voorbeelden

$
\eqalign{
  & 3x(2x - 3) = 6x^2  - 9x  \cr
  &  - 2a(b - 3) =  - 2ab + 6a  \cr
  & (x + 2)(2y - 3) = 2xy - 3x + 4y - 6  \cr
  & (x + 2)(x - 3) = x^2  - x - 6  \cr
  &  - 4a( - 4a - 3) = 16a^2  + 12a  \cr
  & (3x + 4)^2  = 9x^2  + 24x + 16  \cr
  & (5 - x)^2  = 25 - 10x + x^2   \cr
  & (x - 5)(x + 5) = x^2  - 25  \cr
  & (a + t)(a + t) = a^2  + 2at + t^2   \cr
  & (4x - 1)(4x + 1) = 16x^2  - 1  \cr
  & (4x - 1)^2  = 16x^2  - 8x + 1  \cr
  & (2x + 6)(4y - 6) = 8xy - 12x + 24y - 36 \cr}
$

$
\eqalign{
& - 3( - x + 2) = 3x - 6 \cr
& (3x - 1)(3x - 2) = 9x^2 - 9x + 2 \cr
& (3x - 1)(3x - 1) = 9x^2 - 6x + 1 \cr
& (3x - 1)(3x + 1) = 9x^2 - 1 \cr
& - 2x( - x - y^2 ) = 2x^2 + 2xy^2 \cr
& \frac{1}
{3}\left( {18x - 27} \right)^2 = 4x^2 - 12x + 9 \cr
& - 3x( - x^2 + 2x) = 3x^3 - 6x^2 \cr
& (x - y)(x + 2y) = x^2 + xy - 2y^2 \cr
& (a^3 - 3)(a^3 + 3) = a^6 - 9 \cr
& (a^3 - 3b)(a^3 + 3b) = a^6 - 9b^2 \cr
& (a^3 - b^2 )(a^3 + c) = a^6 + a^3 c - a^3 b^2 - b^2 c \cr}
$

©2004-2020 Wiskundeleraar - login